Isolation and characterization of the thrombin-like enzyme from Cryptelytrops albolabris (white-lipped tree viper) venom - Tan, N.H.; Fung, S.Y.; Yap, Y.H.Y. (2012)
A thrombin-like enzyme (termed albolabrase) was isolated in purified form from the venom of Cryptelytrops albolabris (white-lipped tree viper) using high performance anion ion exchange and gel filtration chromatography. The molecular mass of albolabrase was 33.7 kDa as determined by SDS-PAGE and 35.8 kDa as determined by Superose gel filtration chromatography. The N-terminal sequence was determined to be VVGGDECNINE which is homologous to many snake venom thrombin-like enzymes. Albolabrase exhibits both arginine ester hydrolase and arginine amidase activities and the enzyme is fastidious towards tripeptide chromogenic anilide substrates. The fibrinogen clotting activity was optimum at 3 mg/mL bovine fibrinogen, and showed distinct species differences in the following decreasing order: bovine fibrinogen > dog fibrinogen â human fibrinogen > goat fibrinogen. The enzyme failed to clot both rabbit and cat fibrinogens. Reversed-phase HPLC analysis on the breakdown products of fibrinogenolytic action of albolabrase indicated that the enzyme belongs to the AB class of snake venom thrombin-like enzyme. In the indirect ELISA, IgG anti-albolabrase reacted extensively with most crotalid venoms, except with Tropidolaemus wagleri and Calloselasma rhodostoma venoms. The double sandwich ELISA, however, showed that anti-albolabrase reacted strongly only with venoms from the Trimeresurus complex, and that the results support the proposed new taxonomy changes concerning the Trimeresurus complex.